(untitled) (Praxis Educativa, 2021)
In this dossier, we propose to install the question about criticism, about how to remain critical in times of digitization of culture that seems to drag with it precisely any perspective of knowing that is not willing to think beyond the drifts of applicability. In this sense, educational research opens as a journey, as a search for readings, techniques, developments and forms of conceptualization that bring us closer to understanding what schooling is being today. The group of articles that make up this special dossier on educational research opens up new meanings, as thresholds that project us to take the floor in public affairs and delves into the threads, the power relations and the crystallizations of such a social practice. Central as is the one that allows those who come to the world to be part of it.